Research Progress of Ferroptosis Regulatory Network and Bone Remodeling in Osteoporosis - Yan, Chunlu; Zhang, Jinlong; An, Fangyu; Wang, Jiayu; Shi, Yao; Yuan, Lingqing; Lv, Donghui; Zhao, Yanzhen; Wang, Yongfeng (Frontiers in Public Health, 2022)
Ferroptosis was induced the programmed cell death with iron overload Fenton reaction. Currently, ferroptosis has not been studied thoroughly. Existing studies have confirmed that ferroptosis involves the metabolisms of the Fe, lipids, amino acid, each mechanism is mutually independent but interrelated, and they are formed a complex regulatory networkeach. Other evidence supports that ferroptosis is participated osteoporotic bone remodeling, predominantly affecting the interaction between bone formation and bone resorption, explicitly bone resorption exceeded bone formation. Based on previous studies, this essay will summarize the regulatory network mechanism of ferroptosis on bone remodeling, and reveal the role of ferroptosis in osteoporosis(OP).